CrysDev : a developer's guide to integrating Crystal reports - Berntson, Craig; Jurden, Dan (Hentzenwerke Pub., 2003)
Annotation Crystal Reports is a powerful reporting tool that can seamlessly integrate into your application. In Crystal Reports Application Development, Craig Berntson shows you how to take advantage of the RDC so you can provide your users with printing, previewing, and report design capabilities. You'll also learn how to determine which components to distribute and how to troubleshoot problems when they occur on the user's computer. If you're developing reporting tools with Crystal Reports, this is a must have book.